Enhanced degradation of lindane in water by sulfite-assisted ultrasonic (SF/US) process: The critical role of generated aqueous electrons - Alin Xia; Haitao Yu; Longyuan Tan; Laxiang Yang (Ultrasonics Sonochemistry)
Persistent pesticides pose significant environmental and health risks due to their strong resistance to conventional degradation methods. This study investigates the degradation of lindane (LND), a perchlorinated pesticide, using a sulfite-assisted ultrasonic (SF/US) process, focusing on the critical role of aqueous electrons (eaq–) in reductive dechlorination. Aqueous electrons were indirectly identified as the primary reactive species in the SF/US system for pollutant degradation, providing insights into US-induced reduction mechanisms. The SF/US system significantly enhanced LND removal, achieving 99.4 % ± 1.0 % degradation within 100 min, compared to 88.9 % ± 1.5 % under ultrasound alone. Kinetic analysis showed that sulfite addition nearly doubled the reaction rate constant (from 0.022 to 0.041 min−1), confirming that eaq– drive LND degradation more efficiently than hydroxyl radicals (HO•). Scavenging experiments further demonstrated that nitrate strongly inhibited degradation, while tert-butanol (TBA) had minimal effect, verifying that eaq–, rather than HO•, dominate the process. The efficiency of SF/US was influenced by various factors, with optimal removal achieved at 200 kHz, oxygen-depleted conditions, and pH 10. The degradation pathway primarily involved sequential reductive dechlorination of LND, progressing through pentachlorocyclohexene, tetrachlorocyclohexadiene, and trichlorobenzene intermediates before ultimately forming non-toxic aromatic derivatives such as hydroquinone and phenol. These findings highlight SF/US as a novel and highly efficient strategy for the remediation of chlorinated pesticides in water treatment.